Prognostic factors for normal postnatal growth rate in low birth weight infants - Setya Wandita, Kristia Hermawan Djauhar Ismail (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Postnatal growth restriction in low birth weight infants is associated with long term adverseneuro-developmental sequel. Meanwhile, infants with excessive weight gain in early weeks oflife have a greater likelihood of later obesity, cardiovascular disease, and diabetes. Identifyingfactors associated with acceptable growth rate in low birth weight infants is important toprevent this potential long term morbidity. The aim of this study was to identify factors associatedwith acceptable growth rate in low birth weight infants. Prospective cohort study was conductedamong 73 low birth weight infants. Growth rate of these infants was determined by serialweight measurement during perinatal care and after being discharged until 46 â 50 weeks postmenstrual age. Growth rate was considered normal if average daily weight gain is 10 â 20 g/kg/day. Factors associated with this acceptable growth rate were analyzed by univariate andmultivariate statistical analysis. Normal growth rate was found in 62.7% subjects (42/67).Significant rate difference of average daily growth was found between small for gestational age(SGA) infants and appropriate for gestational age (AGA) infants (mean difference -2.90 g/kg/day; 95%CI: -5.68 - -0.12). The SGA infants had a greater risk for gaining weight below acceptablegrowth rate (adjusted RR= 2.9; 95%CI: 1.1 â 8.5). In conclusion, SGA is the only factor whichcan be associated with normal growth rate in low birth weight infants. Moreover, SGA infantsare in a greater risk for having slower growth rate compared to AGA.Keywords: growth rate - post natal - low birth weight â prognostic - gestational rate